Fundamentals of building construction : materials and methods - Allen, Edward, 1938-; Iano, Joseph (Hoboken : Wiley, 2013)
'Now in its sixth edition, this bestselling reference focuses on the basic materials and methods used in building construction. Emphasizing common construction systems such as light wood frame, masonry bearing wall, steel frame, and reinforced concrete construction, the new edition includes new information on building materials properties; the latest on'pre-engineered' building components and sustainability issues; and reflects the latest building codes and standards. It also features an expanded series of case studies along with more axonometric detail drawings and revised photographs for a thoroughly illustrated approach'--
'The book is necessarily complex without being complicated. It avoids the dilemma of having to expand ad infinitum over time by presenting the basic construction systems, each in sufficient detail that the student is brought to an operational level of knowledge. It deals, as its subtitle indicates, with fundamentals. In this latest edition, we have updated and revised many portions of the text'--
Includes index.
Keywords: Building; Building materials